Hospital service reconfiguration: the battle for hearts and minds. (16th February 2012) - Barratt, Helen; Raine, Rosalind
Abstract : Will Andrew Lansley's four tests for reconfiguration make decisions less controversial? Helen Barratt and Rosalind Raine discuss the challenges they raise